A 3D-printed patient-specific modular implants for pelvic reconstruction of bone tumors involving the sacroiliac joint - Lv, Zhaorui; Li, Zhenfeng; Yang, Qiang; Li, Jianmin (Frontiers in Bioengineering and Biotechnology, 2023)
Current reconstruction methods of the pelvic ring after extensive resection of tumors involving the sacroiliac joint have a high incidence of failure. We aimed to study the effect of 3D-printed patient-specific implant reconstruction to show that this method is stable and has a low risk of failure.Between February 2017 and November 2021, six patients with bone tumors involving the sacroiliac joint (Enneking I+IV) who received 3D-printed patient-specific implants for pelvic reconstructive surgery were retrospectively analyzed. Two female and four male patients with a mean age of 41.83 years (range 25-65 years) were included. Two were osteosarcomas, two chondrosarcomas, one malignant fibrous histiocytoma, and one giant cell tumor of bone. For each patient, preoperative osteotomy guides were designed to ensure accurate tumor resection and individualized prostheses were designed to ensure a perfect fit of the bone defect. General, oncologic, and functional outcomes, implant status, and complications were retrospectively analyzed. The Visual Analog Scale (VAS) was used to assess pain and the Musculoskeletal Tumor Society (MSTS) score was used to assess hip function. Osseointegration was assessed by CT.According to the preoperative design, complete resection of the entire tumor and reconstruction with a custom 3D-printed sacroiliac joint implant was completed without perioperative severe complications or deaths. Relatively satisfactory surgical margins were achieved. The mean operative time and intraoperative blood loss were 495 minutes (420-600 minutes) and 2533.33 mL (range, 1200-3500 mL), respectively. The mean follow-up was 49.83 months (range, 18-75 months). At the last follow-up, all four patients were disease-free, and the two patients who developed lung metastases were alive with tumors. All patients could walk unassisted. The mean VAS was 1.33 (range, 0-2). The mean MSTS score was 25.33 (range, 24-27).CT showed complete osseointegration of the implant to the ilium and sacrum.The 3D-printed custom prosthesis can effectively reconstruct pelvic stability after total sacroiliac joint resection with satisfactory clinical results.